1999
DOI: 10.1021/jp991843j
|View full text |Cite
|
Sign up to set email alerts
|

An XPS Study of the Interaction of Ultrathin Cu Films with Pd(111)

Abstract: The interaction of ultrathin Cu films with Pd(111) was studied by X-ray photoelectron spectroscopy (XPS). The effects of Cu coverage and annealing temperature were investigated. The XPS data show that at room temperature Cu grows on Pd(111) layer-by-layer without alloying. Furthermore, Cu 2p 3/2 core-level shifts as a function of film thickness indicate that the Cu-Pd interactions perturb the electronic properties of two to three layers of Cu atoms. The Cu 2p 3/2 binding energy of a Cu monolayer at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
59
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 43 publications
10
59
0
Order By: Relevance
“…33 More precisely, the stripe, triangular, and honeycomb structures seen in experiments at two, three, and four monolayers, respectively, were very similar to those obtained from simulations in which V 0 was lowered from 0.015 to V 0 = 0.0032,0.00087, and 0.00043, respectively (see Ref. 33 for a direct comparison of simulation and experimental 47,48 point to layer-bylayer growth at room temperature. No alloying is observed and a recovery of the Cu incommensurate lattice spacing takes place for coverages larger than 4 ML.…”
Section: F Comparison With Experimental Data and Model Predictionssupporting
confidence: 70%
“…33 More precisely, the stripe, triangular, and honeycomb structures seen in experiments at two, three, and four monolayers, respectively, were very similar to those obtained from simulations in which V 0 was lowered from 0.015 to V 0 = 0.0032,0.00087, and 0.00043, respectively (see Ref. 33 for a direct comparison of simulation and experimental 47,48 point to layer-bylayer growth at room temperature. No alloying is observed and a recovery of the Cu incommensurate lattice spacing takes place for coverages larger than 4 ML.…”
Section: F Comparison With Experimental Data and Model Predictionssupporting
confidence: 70%
“…11). Previously reported experimental and theoretical studies of bulk and surface Pd-Ag alloys have shown that the low BE of Ag3d in these materials is due to the modified screening of the Ag3d core hole associated with the high density of valence electrons of Pd near the Fermi level [83,84]. Although the Ag3d BEs in PdAg MCs and PdAg NPs are comparable, the BE of Pd3d in the former shows a negative BE shift relative to the latter.…”
Section: Geometric And/or Electronic Effectsmentioning
confidence: 93%
“…Experimentally it has been found that the growth of Cu is layer-by-layer at room temperature. [10][11][12] In the submonolayer regime the substrate becomes gradually covered by two-dimensional ͑2D͒ islands. 10 Although near 1 ML coverage there is some indication of dislocations, 10,12,13 only at 2-3 ML the average lattice constant reduces to the relaxed value.…”
mentioning
confidence: 99%
“…[10][11][12] In the submonolayer regime the substrate becomes gradually covered by two-dimensional ͑2D͒ islands. 10 Although near 1 ML coverage there is some indication of dislocations, 10,12,13 only at 2-3 ML the average lattice constant reduces to the relaxed value. This has been interpreted as a transition to relaxed morphology 11,12 leading to the conclusion that the pseudomorphic structure is stable up to 2-3 ML.…”
mentioning
confidence: 99%